A systematic review of qualitative literature on antimicrobial stewardship in Sub-Saharan Africa - George James Porter; Stephen Owens; Matthew Breckons (BMC, 2021)
Abstract Background Antibiotic resistance is a major problem in every region of the globe and Sub-Saharan Africa (SSA) is no exception. Several systematic reviews have addressed the prevalence of resistant organisms but few have examined the underlying causes in this region. This systematic review of qualitative literature aims to highlight barriers and facilitators to antimicrobial stewardship in SSA. Methods A literature search of Embase and MEDLINE(R) was carried out. Studies were included if they were in English, conducted in SSA, and reported qualitative data on the barriers and facilitators of antimicrobial stewardship or on attitudes towards resistance promoting behaviours. Studies were screened with a simple critical appraisal tool. Secondary constructs were extracted and coded into concepts, which were then reviewed and grouped into themes in light of the complete dataset. Results The literature search yielded 169 results, of which 14 studies from 11 countries were included in the final analysis. No studies were excluded as a result of the critical appraisal. Eight concepts emerged from initial coding, which were consolidated into five major themes: ineffective regulation, health system factors, clinical governance, patient factors and lack of resources. The ineffective regulation theme highlighted the balance between tightening drugstore regulation, reducing over-the-counter sale of antibiotics, and maintaining access to medicines for rural communities. Meanwhile, health system factors explored the tension between antimicrobial stewardship and the need of pharmacy workers to maintain profitable businesses. Additionally, a lack of resources, actions by patients and the day-to-day challenges of providing healthcare were shown to directly impede antimicrobial stewardship and exacerbate other factors which promote resistance. Conclusion Antibiotic resistance in SSA is a multi-faceted issue and while limited resources contribute to the problem they should be viewed in the context of other factors. We identify several contextual factors that affect resistance and stewardship that should be considered by policy makers when planning interventions. This literature base is also incomplete, with only 11 nations accounted for and many studies being confined to regions within countries, so more research is needed. Specifically, further studies on implementing stewardship interventions, successful or not, would be beneficial to inform future efforts.